2020
DOI: 10.1177/1934578x20912863
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of the Potent Antimicrobial Metabolite “Terrein” From the Fungus Aspergillus terreus

Abstract: The endophytic fungus Aspergillus terreus (JAS-2) derived from Achyranthes aspera possesses multiple bioactive metabolites, one of which is terrein, a potent antimicrobial substance. Here we report the improved biosynthesis of terrein in cultures grown in media with a fixed carbon and modified nitrogen source (4% dextrose, 1% casein) for 15 days, after which pure crystals of terrein were obtained in the culture medium. We suggest that our improved method is effective for improving the quantity and quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[25] The latter was cultured in a modified SDB medium containing a fixed carbon source and a modified nitrogen source (4 % glucose, 1 % casein) at 26 °C for 15 days, the concentration of metabolite reached its maximum, which was estimated as 1.14 g/ L. It is worth noting that the fermentation metabolites slowly evaporate in the broth (incubate at 20 °C for 15 days), directly crystallizing the compound terrein. [26]…”
Section: Increased Production Of Terreinmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] The latter was cultured in a modified SDB medium containing a fixed carbon source and a modified nitrogen source (4 % glucose, 1 % casein) at 26 °C for 15 days, the concentration of metabolite reached its maximum, which was estimated as 1.14 g/ L. It is worth noting that the fermentation metabolites slowly evaporate in the broth (incubate at 20 °C for 15 days), directly crystallizing the compound terrein. [26]…”
Section: Increased Production Of Terreinmentioning
confidence: 99%
“…As mentioned above, Birch et al believed that terrein was synthesized through the polyketide pathway through the isotope tracing method. [26] Hill et al demonstrated the biosynthesis of terrein through the contraction of the aromatic ring of intermediate 2 through the incorporation experiment of potential aromatic precursors. [27] Zaehle and colleagues accidentally discovered terrein biosynthesis gene locus in 2014, and further identified 2 as terrein biosynthesis intermediate.…”
Section: Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Fluopsin C, a bioactive secondary metabolite (a metal-containing antibiotic) extracted from Streptomyces and Pseudomonas species , showed effective antimicrobial activities against Gram-positive, Gram-negative, and drug-resistant bacteria [ 42 , 43 ], Sharma 2020). Terrein is another purified metabolite extracted from the fungus that showed better antimicrobial activities against S. aureus, A. hydrophila , E. Faecalis, and other microbes [ 44 ]. Therefore, we suggested that after clinical approval these molecules could be used as potential drugs against colistin-resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms have been shown to be inhibited by bioactive substances obtained from nature. [11][12][13][14] Aspergillus sp., a filamentous fungus, is well known for its potent antibacterial properties. [15][16][17] Inhibition of virulence factors and direct harm to the K. pneumoniae are known antibacterial mechanisms of Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%